2013
DOI: 10.1521/pedi.2013.27.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Disorder in Four Different Age Groups: A Cross-Sectional Study of Community Residents in Germany

Abstract: Studies examining the natural course of borderline personality disorder (BPD) over the life span have yielded declining prevalence rates in older age groups. However, there is evidence that different BPD symptoms have different longitudinal patterns, with impulsivity decreasing with advancing age and negative affect remaining stable into late adulthood. However, since all studies dealt with treated, clinical samples of BPD patients, it is not yet known whether this represents the natural course of BPD symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 55 publications
5
17
0
1
Order By: Relevance
“…Moreover, we found a significant influence of age. This is in line with former results where younger age was associated with SAD [Grant et al, 2005] and leads to the consideration that SAD decreases during the course of life as it has already been found within other psychopathology [e.g., Arens et al, 2013]. However, it was unexpected that we found an increased susceptibility for SAD within carriers of the l/l genotype.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we found a significant influence of age. This is in line with former results where younger age was associated with SAD [Grant et al, 2005] and leads to the consideration that SAD decreases during the course of life as it has already been found within other psychopathology [e.g., Arens et al, 2013]. However, it was unexpected that we found an increased susceptibility for SAD within carriers of the l/l genotype.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the associations with trauma exposure, younger age was associated with higher levels of PTSD, DSO, and BPD; this is a result consistent with an extensive literature demonstrating that younger individuals are more likely to experience multiple forms of psychopathology, including PTSD (Frueh, Grubaugh, Acierno, Elhai, Cain, & Magruder, 2007) and BPD (Arens et al, 2013). We also found that women had higher levels of PTSD than men, which is consistent with what has been reported in much of the trauma literature (Tolin & Foa, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Dimensional stability demonstrated moderate stability (Bornovalova et al, 2009;Chanen et al, 2004;Cohen et al, 2008). On average, BPD symptoms appear in adolescence, peak in early adulthood, and then decline (Arens et al, 2013;Chanen & Kaess, 2012). The balance of evidence suggests that while impulsive-type symptoms do reduce over time, affective-type symptoms, which include negative affect and feelings of emptiness, are more likely to persist (Meares, Gerull, Stevenson, & Korner, 2011).…”
Section: Onset Stability and Coursementioning
confidence: 99%